2018
DOI: 10.3390/ph11030061
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Pathway Enrichment Analysis for Targeting Comorbid Diseases via Network Endopharmacology

Abstract: The past decades have witnessed a paradigm shift from the traditional drug discovery shaped around the idea of “one target, one disease” to polypharmacology (multiple targets, one disease). Given the lack of clear-cut boundaries across disease (endo)phenotypes and genetic heterogeneity across patients, a natural extension to the current polypharmacology paradigm is to target common biological pathways involved in diseases via endopharmacology (multiple targets, multiple diseases). In this study, we present pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 71 publications
0
26
0
Order By: Relevance
“…Additionally, this study examined genes found in the subject's blood, which may not translate directly to expression within the subject's brain in all cases. Many of the known key players in Alzheimer's disease, such as APP, are differentially expressed between tissue types and between different regions of the brain [48]. With that being said, with further study these genes may prove to be valuable biomarkers for use in much-needed early diagnosis tests, as many of the genes show similar expression patterns and relationships in both MCI and AD individuals and blood is a relatively easily obtained sample.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this study examined genes found in the subject's blood, which may not translate directly to expression within the subject's brain in all cases. Many of the known key players in Alzheimer's disease, such as APP, are differentially expressed between tissue types and between different regions of the brain [48]. With that being said, with further study these genes may prove to be valuable biomarkers for use in much-needed early diagnosis tests, as many of the genes show similar expression patterns and relationships in both MCI and AD individuals and blood is a relatively easily obtained sample.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatic approaches applied to targets, biomarkers, drug characteristics, and drug-disease pathway proximity will facilitate matching drug processes to disease pathways and assist in developing a robust TS approach. Application of a multiattribute utility theory to develop weighting of TS elements may improve predictability [95, 96].…”
Section: Discussionmentioning
confidence: 99%
“…The drug repurposing candidates that can target common mechanisms involved in T2DM and AD have recently gained attention due to the increased comorbidity among such cases [136]. In the paper of Aguirre-Plans et al [137] authors proposed a novel drug repurposing approach, Proximal pathway Enrichment Analysis"-a powerful computational strategy for targeting multiple pathologies involving common biological pathways in T2DM and AD. 35 of evaluated pathways are shared by both disease entities.…”
Section: Treating Ad With Diabetic Medicationsmentioning
confidence: 99%